A prospective study of maternal risk factors for low birth weight babies in Maiduguri, North-Eastern Nigeria - Takai, Idris; Bukar, Mohammed; Audu, Bala (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background/Aim: Low birth weight (LBW) is associated with a higher risk of mortality and long term consequences for the survivors. This study determines the incidence and risk factors for LBW babies in Maiduguri. Context/Setting: This study was done in the Departments of Obstetrics and Gynaecology of the University of Maiduguri Teaching Hospital and the State Specialist Hospital, Maiduguri. Materials and Methods: This was a prospective study involving 854 pregnant women and their babies between 2nd February 2009 and 29th July 2009. Socio-demographic, obstetric, medical factors, obstetrics interventions and foetal birth weights were obtained and recorded. Association between variables were examined using student’s t-test and Chi-squared test and multivariate logistic regression analysis aP< 0.05 was considered significant. Results: The incidence of LBW was 16.9%. The risk factors for LBW were non-use of haematinics index pregnancy (OR = 13.04; 95% CI = 12-36; Pvalue 0.000); previous history of stillbirth (OR = 8.11; 95% CI = 6-19; Pvalue 0.000); hypertensive disorders of pregnancy (OR = 6.12; 95% CI = 5-14; Pvalue 0.000); ante-partum haemorrhage (OR = 5.85; 95% CI = 4-9; Pvalue 0.000); less than 4 ANC visitsn (OR = 4.94; 95% CI = 3-12; Pvalue 0.000); previous history of premature delivery (OR = 4.39; 95% CI = 4-11;Pvalue 0.000); previous history of LBW (OR = 3.65; 95% CI = 2-21; Pvalue 0.000) and non-use of intermittent preventive therapy in the index pregnancy (OR = 3.24; 95% CI = 1-16; Pvalue 0.001); and teenage mother (OR = 2.75; 95% CI = 2-27; Pvalue 0.006). Conclusion: This study showed high incidence of LBW. Obstetric factors (problems and intervention of the current pregnancy) and previous obstetric performances played crucial role in the occurrence of LBW in our study. Qualitative antenatal care should be made available and provided to pregnant women at all levels of care.